A Model for the Effect of Low Temperature and Poor Light on the Growth of Cucumbers in a Greenhouse - Fengyin Zhang; Jing Luo; Changhong Yuan; Chunying Li; Zaiqiang Yang (Agronomy, 2022)
With the expansion of cucumber cultivation, many growers continue to experience extreme weather and environmental issues. This study aimed to examine and model the effects of low temperature (LT) and poor light (PL) stresses on cucumber growth. The experiment was designed as an orthogonal experiment that analyzed temperature, light, and duration. The daily maximum/minimum temperatures of the experiment were set as per the following four levels: 13 °C/3 °C, 16 °C/6 °C, 19 °C/9 °C, 22 °C/12 °C, and the control at 28 °C/18 °C. The light was divided into two levels: 200 μmol∙m−2∙s−1 and 400 μmol∙m−2∙s−1, with 800 μmol∙m−2∙s−1 as the control. Treatment duration was set at 2, 5, 8, and 11 days. Stress with different LT, PL, and duration was expressed using the stress effect (0–1), which decreased with an increase in stress level. Meanwhile, treatment with a temperature of 3 °C and light of 400 μmol∙m−2∙s−1 for 11 days had the smallest effect on stress, which was only 67% of that of the control following 50 days of recovery, and had the most severe effect on cucumber growth. The proportion of dry weight allocated to leaves and stems decreased with increasing low temperatures and poor light stress, but the proportion allocated to fruit increased. The highest percentage of fruit distribution was found in the treatment with temperature of 9 °C, light of 200μmol∙m−2∙s−1, and 11 days duration, being 3.57 times higher than the control. In order to better investigate the effects of LT and PL stress on cucumber growth, light and temperature effect (LTE), growing degree days (GDD), and product of thermal effectiveness and PAR (TEP) models were developed based on temperature and light. The root mean square error (RMSE) of the LTE model was found to be 4.214 g∙plant−1, 36.3% of that of the GDD model and 78.8% of that of the TEP model, better simulating the above-ground dry weight of cucumber plants.